2016
DOI: 10.2174/1874325001610010669
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Early Debridement in Treatment of Acute Periprosthetic Joint Infections After Hip and Knee Replacements

Abstract: Background:Periprosthetic Joint Infection Remains a Dreaded Complication After Hip and Knee Replacement Surgery.Treatment Options for Acute Postoperative and Acute Hematogenous Infections Include Arthroscopic or Open Debridement With Retention or Exchange of the Prostheses. This Review Article Aims to Summarize the Evidence for Management of Acute Postoperative And Acute Hematogenous Infections.Methods:A Systematic Literature Search Was Performed Using a Computer-based Search Engine Covering Medline (OvidSP), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 76 publications
1
12
0
Order By: Relevance
“…Most of our infection control rates of DAIR procedures are comparable to the overall pooled success rate of 61.4 % reported in a recent meta-analysis (Kunutsor et al, 2018). However, some other retrospective studies have reported higher infection control rates for DAIR procedures (Byren et al, 2009;Sendi et al, 2017;Volpin et al, 2016;Wouthuyzen-Bakker et al, 2020). The relatively large number of patients a S. capitis (n = 2), S. warneri (n = 1), S. haemolyticus (n = 1) and S. pseudintermedius (n = 1).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Most of our infection control rates of DAIR procedures are comparable to the overall pooled success rate of 61.4 % reported in a recent meta-analysis (Kunutsor et al, 2018). However, some other retrospective studies have reported higher infection control rates for DAIR procedures (Byren et al, 2009;Sendi et al, 2017;Volpin et al, 2016;Wouthuyzen-Bakker et al, 2020). The relatively large number of patients a S. capitis (n = 2), S. warneri (n = 1), S. haemolyticus (n = 1) and S. pseudintermedius (n = 1).…”
Section: Discussionsupporting
confidence: 82%
“…Nonetheless, even more than 6 weeks after the index arthroplasty an eradication rate of 60 % can be achieved when performing DAIR (Löwik et al, 2019). The success rate of DAIR for early postoperative infection is better than for hematogenous infections (Volpin et al, 2016;Wouthuyzen-Bakker et al, 2020). There is no place for DAIR in the treatment of chronic infections (Sukeik and Haddad, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…in a previously well-functioning implant [12,14,15]. In haematogenous infections, a full workup to establish the source of infection should be undertaken preoperatively, including a comprehensive history of recent systemic infections or invasive procedures causing bacteremic seeding of the hip, and investigations should include a throat swab, chest radiograph, and urine, stool and blood cultures [14].…”
Section: Protocolmentioning
confidence: 99%
“…An aggressive open debridement with exchange of mobile parts and retention of the implant in stable components with no evidence of immunosuppression, and overlying soft tissue and skin of good condition is associated with good results of infection control, especially when the infection is diagnosed within the first week after the index procedure [13][14][15]17,18]. The aim of rapid intervention with thorough open debridement is to prevent the production of any biofilm by the infecting organism, paramount for successful treatment of infection [7,19].…”
Section: A) Cemented Prosthesesmentioning
confidence: 99%
See 1 more Smart Citation